Isolated V-Lesion Early after Kidney Transplantation May Not Truly Represent a Rejection. (July 2018) - Wohlfahrtova, Mariana; Hruba, Petra; Novotny, Marek; Klema, Jiri; Krejcik, Zdenek; Stranecky, Viktor; Honsova, Eva; Vichova, Petra; Viklicky, Ondrej
Abstract : Background: Acute vascular rejection (AVR) is known to be a negative prognostic factor for kidney allograft survival. However, a role of early isolated v-lesion (IV) defined as intimal arteritis with minimal tubulointerstitial inflammation (TI) is unclear. While some authors believe in hidden ischemic/reperfusion injury, others are convinced of its rejection origin. However, current Banff classification assesses IV as type 2 or 3 of acute T-cell or antibody mediated rejection. To help resolve if IV truly represents acute rejection, molecular profiling of IV and T-cell mediated vascular rejection (TCMRV) was performed. Materials and Methods: Gene expression profile of early IV (n=6) and TCMRV (n=4) within 1st month after kidney transplantation was compared using microarrays (Illumina Human HT-12 v4 Expression BeadChips). Differentially expressed genes were defined as those with fold change > 2 and adjusted p-value <0.05 corrected for multiple testing. The enrichment of dysregulated genes in biological processes was analysed using DAVID database. Results: Using microarray-based gene expression profiling in a training set of patients (n= 10), we identified 288 upregulated and 22 downregulated genes in early TCMRV compared to IV These dysregulated genes were primarily associated with T and B cell activation, costimulation, differentiation, receptor signalling pathway, antigen processing and presentation indicating higher innate and adaptive immune response and inflammation in early TCMV biopsies (Table 1). Hierarchical clustering and principal component analysis (Fig. 3) applied to the whole microarray data indicated a clear distinction in kidney allografts with TCMRV and IV. Our findings were verified in an independent validation set of patients (n = 20) using RT-qPCR and confirmed increased expression of genes associated with immunity and inflammation in TCMRV. Figure. No caption available. Figure. No caption available. Figure. No caption available. Figure. No caption available. Discussion: Our study provides a resource for better understanding the origin of isolated v-lesion and are in agreement with recent literature evidence which shows that intimal arteritis has probably less importance in diagnostics of TCMR than TI infiltrate. Furthermore, absence of TI inflammation in biopsies with IV makes TCMRV very unlikely (Reeves et al., Am J Transplant 2016). Conclusion: Early isolated v-lesion has transcriptional profile of immune injury of significantly lower extend compared to T-cell mediated vascular rejection. According to this genome-wide transcriptome analysis early IV may feature non-rejection phenotype. Our findings call for reassessment of current histopathology classification which considers intimal arteritis to be at least grade 2 of T-cell mediated rejection irrespective of TI inflammation. Although more emphasis is placed in research on detrimental humoral phenotype, larger investigation is warranted to provide insight into cellular phenotype of AVR after kidney transplantation. Supported by Ministry of Health of the Czech Republic, grant nr. 15-26519A and 17-29992A.